Factors associated with public injection and nonfatal overdose among people who inject drugs in street-based settings. (2nd January 2018) - Vallance, Kate; Pauly, Bernie; Wallace, Bruce; Chow, Clifton; Perkin, Kathleen; Martin, Gina; Zhao, Jinhui; Stockwell, Tim
Abstract: Background: In 2016, BC Canada declared a public health emergency in response to increasing illicit drug overdose deaths. Previous research has shown that adverse social conditions including unstable housing and insufficient harm reduction services can exacerbate public injection and overdoses. Methods: Cross-sectional interview data from Victoria (2008–2015) and Vancouver (2008–2012), BC ( n = 548) were analysed using multivariate logistic regression models to assess differences in risks and harms for people 19+ who inject drugs in street-based settings. Results: Living in Victoria (OR: 5.55, 95%CI: 3.44–8.95; p < 0.001), having unstable housing (OR: 4.24, 95%CI: 2.75–6.54; p < 0.001), injecting daily (OR: 2.24, 95%CI: 1.40–3.58; p < 0.001), sharing needles (OR: 3.00, 95%CI: 1.22–7.38; p < 0.05), and sexual minority status (OR: 2.14, 95%CI: 1.06–4.34; p < 0.05) were significantly associated with increased risk of public injection. Being older (OR: 0.96, 95%CI: 0.94–0.99; p < 0.01), identifying as Indigenous (OR: 0.58, 95%CI: 0.34–0.98; p < 0.05) and later survey year (OR: 0.83, 95%CI: 0.74–0.93; p < 0.001) were associated with a decreased risk of public injection. Living in Victoria (OR: 2.21, 95%CI: 1.30–3.75; p < 0.01) was significantly associated with higher risk of overdose and being older (OR: 0.96, 95%CI: 0.94–0.99; p < 0.01) was associated with decreased risk. Conclusions: Mitigating risk environments for public injection and overdose requires attention to micro- and macro-level factors. Overall findings indicate that implementation of a supervised injection facility in Victoria would likely reduce public injection and overdoses.